Ferroptosis Holds Novel Promise in Treatment of Cancer Mediated by Non-coding RNAs - Zhi, Yuan; Gao, Ling; Wang, Baisheng; Ren, Wenhao; Liang, Kristina Xiao; Zhi, Keqian (Frontiers in Cell and Developmental Biology, 2021)
Ferroptosis is a newly identified form of regulated cell death that is associated with iron metabolism and oxidative stress. As a physiological mechanism, ferroptosis selectively removes cancer cells by regulating the expression of vital chemical molecules. Current findings on regulation of ferroptosis have largely focused on the function of non-coding RNAs (ncRNAs), especially microRNAs (miRNAs), in mediating ferroptotic cell death, while the sponging effect of circular RNAs (circRNAs) has not been widely studied. In this review, we discuss the molecular regulation of ferroptosis and highlight the value of circRNAs in controlling ferroptosis and carcinogenesis. Herein, we deliberate future role of this emerging form of regulated cell death in cancer therapeutics and predict the progression and prognosis of oncogenesis in future clinical therapy.